2002
DOI: 10.1046/j.1365-2958.2002.02901.x
|View full text |Cite
|
Sign up to set email alerts
|

Polar localization of the Escherichia coli oriC region is independent of the site of replication initiation

Abstract: Summary The location of the origin‐linked region of the Escherichia coli chromosome was analysed in strains lacking the core origin locus, oriC. In these strains, which initiate replication from F factors integrated at different locations around the chromosome, origin‐linked DNA remains localized near the cell poles, as in wild‐type cells. In contrast, minichromosomes containing 7 kb of chromosomal DNA including oriC are generally excluded from the ends of the cell. Thus, we propose that positioning of the wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
20
1

Year Published

2003
2003
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 24 publications
5
20
1
Order By: Relevance
“…The motive force could be generated by replication itself (29), by the successive insertion of cotranslated gene products into the membrane ("transertion") (51), or by release from sibling chromosome "cohesion" (3,48). Active navigation could be provided by factors acting on a non-parS, origin-linked centromere (12,21) or by actin-like MreB proteins (9,20,25). The only direct evidence that chromosomal parAB loci act in partition is their ability to stabilize unstable vectors carrying cognate parS sites (2,10,34,52).…”
mentioning
confidence: 99%
“…The motive force could be generated by replication itself (29), by the successive insertion of cotranslated gene products into the membrane ("transertion") (51), or by release from sibling chromosome "cohesion" (3,48). Active navigation could be provided by factors acting on a non-parS, origin-linked centromere (12,21) or by actin-like MreB proteins (9,20,25). The only direct evidence that chromosomal parAB loci act in partition is their ability to stabilize unstable vectors carrying cognate parS sites (2,10,34,52).…”
mentioning
confidence: 99%
“…A polar location has been demonstrated for plasmid R1 in E. coli (31) and several naturally occurring plasmids of Agrobacterium tumefaciens and Sinorhizobium meliloti (20). In addition, a cell pole location has been shown for the chromosomal origins of replication of E. coli (12,32), Bacillus subtilis (26), and Caulobacter crescentus (19). In E. coli, a 25-bp sequence within the origin was identified as playing a role in the bipolar migration of a newly replicated oriC region (49).…”
Section: Discussionmentioning
confidence: 98%
“…It appears that the origin-proximal region of the bacterial chromosome plays an analogous role to the eukaryotic centromere. However, although oriC itself is not sufficient for localization (Gordon et al 2002), regions around oriC have been reported to facilitate correct orientation, as will be discussed below (Lin & Grossman 1998;Wu & Errington 2002;Yamaichi & Niki 2004). …”
Section: Orientation Positioning and Movement Of The Bacterial Chrommentioning
confidence: 99%